The Reality of Private Higher Education in Kurdistan Region- Iraq For Period (2010-2020): An Analytical Study - Mohamad Ali, Fahmy; Ali Salih, Shler (Zanco Journal of Human Sciences, 2022)
This researchaims to study the reality and development of private higher education in the Kurdistan Region of Iraq both qualitatively and quantitatively and to determine the problems and challenges that private higher education suffers from in the region that hinder the compatibility between education outcomes and the labor market. The research examined the official data of the Ministry of Higher Education and Scientific Research concerning universities and private institutes in the period 2010-2020. The research adopts the descriptive-analytical method to reach its objectives and solve its problems. The research found that despite the growth in the number of universities, institutes, the number of students and faculty in terms of quantity, this development did not match by qualitative one. Additionally, private higher education in the Kurdistan Region suffers from many problems and challenges, including; The lack of teaching staff in many disciplines and the lack of buildings of their own. In conclusion, the research presented several suggestions, including; Revising the law of private universities in line with the reality and the country's needs and future expectations, encouraging faculty members to increase their scientific knowledge, conducting further research, and reducing scientific promotion procedures. In addition to providing the necessary administrative and financial facilities for investors to implement and increase their investments in the field of constructing and expanding buildings for private universities and institutes.